2008
DOI: 10.1007/s11606-008-0540-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resident Work Hour Limitations on Faculty Professional Lives

Abstract: Resident work hour limitations have had large effects on the professional lives of faculty. These findings may have important implications for recruiting and retaining faculty at academic medical centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…For these items, responders were grouped into categories (Յ40% likelihood vs Ͼ40% likelihood) based on previously published use of this threshold. 12 With respect to hours worked per week, physicians were asked, on average, how many hours per week they spent (1) working on site (eg, physically at work seeing patients, doing research, teaching, or performing administrative tasks), (2) performing work-related tasks at home (eg, preparing talks, writing articles, or working on grants), and (3) keeping abreast of developments in their field (eg, reading journals) or performing tasks to maintain certification (eg, completing American Board of Internal Medicine modules). These 3 values were summed to calculate total hours worked per week.…”
Section: Data Collectionmentioning
confidence: 99%
“…For these items, responders were grouped into categories (Յ40% likelihood vs Ͼ40% likelihood) based on previously published use of this threshold. 12 With respect to hours worked per week, physicians were asked, on average, how many hours per week they spent (1) working on site (eg, physically at work seeing patients, doing research, teaching, or performing administrative tasks), (2) performing work-related tasks at home (eg, preparing talks, writing articles, or working on grants), and (3) keeping abreast of developments in their field (eg, reading journals) or performing tasks to maintain certification (eg, completing American Board of Internal Medicine modules). These 3 values were summed to calculate total hours worked per week.…”
Section: Data Collectionmentioning
confidence: 99%
“…Two studies advance our understanding of the unintended consequences of resident duty hour regulations. A survey of physicians at three hospitals 12 found large negative effects on the professional lives of faculty, and both this study and a national survey of faculty 13 suggest that work hour regulations have impaired the learning environment. We invited an editorial to expand upon these unintended consequences.…”
Section: How Do We Promote Student and Physician Well-being?mentioning
confidence: 57%
“…Needs assessments in this issue include clinical topics of obesity 22 and tobacco dependence, 23 and curriculum design issues such as ward attending rounds, 24 quality of care in ambulatory clinics, 8,9 student career choice, 25,26 resident well-being, 11 and residency training organization. 12,13,27 …”
Section: Where Are the Training Gaps?mentioning
confidence: 99%
“…Additional studies of surgical and internal medicine faculty revealed that institution of the 2003 DHS had negative effects on their ability to teach, resident education, and amount of teaching on rounds. 4,5 As with the 2003 DHS, the new ACGME DHS that went into effect in July 2011 have the potential to affect education and patient care. 1 Studies published on the feasibility of implementation of the 2008 Institute of Medicine recommendations 6 or the impact of the 2011 DHS note potential negative effects on resident education and patient care.…”
Section: Introductionmentioning
confidence: 99%